Potensi Antibakteri dan Antibiofilm Ekstrak Etanol Bunga Bintaro (Cerbera odollam) terhadap Staphylococcus aureus ATCC 6538 - Lestari, Dwi Rahma Suci; Soegianto, Lisa; Hermanu, Liliek S. (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2017)
Cerbera odollam was one of the plants that can inhibit the growth of bacteria that cause infectious diseases. The misuse of antibiotic in the treatment of infection frequent caused bacterial resistance. One of the forms of antibiotic resistance was the capability of microorganism forming biofilm. This study was conducted to determine the antibacterial and anti-biofilm activity of ethanolic extract from Cerbera odollam flower against Staphylococcus aureus. The ethanolic extract obtained by maceration method using 96% ethanol as a solvent. The ethanol extract of Suicide tree (10, 20 and 30%) were tested for antibacterial activity against Staphylococcus aureus using well diffusion method and anti-biofilm activity using microdilution method. Based on the results, ethanol extract of flowers Cerbera odollam inhibit the growth of Staphylococcus aureus with inhibition zone of 21.66±0.73 mm (10%), 25.66±1.50 mm (20%) and 27.10±1.06 mm (30%). The ethanol extract of Suicide tree flower inhibit biofilm formation 98.29% at the concentration of 3.75%. The bio autography results showed that alkaloid and tannin responsible as bioactive compounds from the ethanol extract Suicide tree flower.